2010
DOI: 10.1039/c003954c
|View full text |Cite
|
Sign up to set email alerts
|

On the abundance of non-cometary HCN on Jupiter

Abstract: Using one-dimensional thermochemical/photochemical kinetics and transport models, we examine the chemistry of nitrogen-bearing species in the Jovian troposphere in an attempt to explain the low observational upper limit for HCN. We track the dominant mechanisms for interconversion of N 2 -NH 3 and HCN-NH 3 in the deep, hightemperature troposphere and predict the rate-limiting step for the quenching of HCN at cooler tropospheric altitudes. Consistent with other investigations that were based solely on time-scal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(87 citation statements)
references
References 165 publications
(506 reference statements)
6
81
0
Order By: Relevance
“…Laboratory studies that investigate the kinetics of C 3 H 2 and C 3 H 3 reactions with other hydrocarbon radicals and molecules would aid exoplanet photochemistry studies. Other possible photochemically produced hazes include elemental sulfur (Zahnle et al 2016), elemental phosphorus or other refractory phosphorus species, and refractory products from coupled C 2 H 2 -NH 3 chemistry (e.g., Keane et al 1996;Ferris & Ishikawa 1988;Moses et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory studies that investigate the kinetics of C 3 H 2 and C 3 H 3 reactions with other hydrocarbon radicals and molecules would aid exoplanet photochemistry studies. Other possible photochemically produced hazes include elemental sulfur (Zahnle et al 2016), elemental phosphorus or other refractory phosphorus species, and refractory products from coupled C 2 H 2 -NH 3 chemistry (e.g., Keane et al 1996;Ferris & Ishikawa 1988;Moses et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike on our own solar-system gas giants, hydrazine (N 2 H 4 ) is not a major product of the ammonia photochemistry in our young-Jupiter models because the NH 2 from ammonia photolysis preferentially reacts with the copious amounts of atomic H to produce NH, and eventually N and N 2 , or with CH 3 to form CH 3 NH 2 and eventually HCN. On Jupiter and Saturn, the coupled ammonia-methane photochemistry is less efficient due to the lack of CH 3 present in the tropospheric region where NH 3 is photolyzed (e.g., Kaye & Strobel 1983;Moses et al 2010). However, the hydrazine abundance is very sensitive to temperature and increases significantly as T eff decreases.…”
Section: Sensitivity Of Disequilibrium Chemistry To K Zzmentioning
confidence: 99%
“…These molecules could also be supplied from external sources such as the rings, satellites or interplanetary dust particles. Alternatively, HCN could be produced in the lower atmosphere, provided a mechanism exists to couple the chemistry of methane and other hydrocarbons to tropospheric ammonia (Moses et al 2010). This could be due to vertical mixing of HCN thermochemically generated in the deep interior (Lewis & Fegley 1984), or shock chemistry under the extreme environmental conditions of lightning (e.g., Bar-Nun & Podolak 1985), sufficient to dissociate NH 3 , PH 3 and CH 4 for the generation of HCN and HCP (see below).…”
Section: Hydrogen Cyanide Hcnmentioning
confidence: 99%
“…Chemical equilibrium is achieved kinetically in the deepest, hottest regions of these models, but chemical reactions tend to be slower in the upper, cooler regions. When transport time scales drop below kinetic conversion time scales-at a pressure called the "quench pressure" or "quench level"-transport begins to dominate over chemical kinetics in controlling the species' vertical profiles (e.g., Prinn & Barshay 1977;Lewis & Fegley 1984;Moses et al 2010;. When this situation occurs, the species can be "quenched" at mole fractions that remain constant with altitude above the quench level (and thus diverge from chemical-equilibrium predictions), as long as transport times scales remain shorter than chemical-kinetics time scales.…”
Section: Chemical Modelsmentioning
confidence: 99%
“…also the K zz profiles inferred from Showman et al 2009, as shown in Moses et al 2011). In our kinetics and transport models, the K zz profile influences the quench behavior of molecules like CO, CH 4 , and NH 3 , and the observations themselves may ultimately provide the best means for defining both the K zz values at the quench levels and the pressures at which those quench levels occur (e.g., Bézard et al 2002;Visscher et al 2010b;Moses et al 2010;. However, the broadband photometric eclipse observations obtained to date for GJ 436b are not sufficient to constrain either the composition or thermal profile accurately enough to derive K zz values in such a manner at this time.…”
Section: Chemical Modelsmentioning
confidence: 99%